Amyand's Hernia with Appendicitis: A Case Report and Integrative Review. (10th November 2015) - Feitosa Cavalcante, Jéssica; Melo Teixeira Batista, Hermes; Cavalcante Pita Neto, Ivo; Fernandes Frutuoso, Jairo; Rodrigues Pinheiro, Woneska; Maria Pinheiro Bezerra, Italla; de Abreu, Luiz Carlos; de Menezes Silveira, Gylmara Bezerra
Abstract : Introduction. Inguinal hernia is a common disorder with an estimated prevalence of 1.2% of the entire population and it is 12 times more common in males. Objective. To describe a case of appendix with signs of inflammation in the hernia sac, condition that is rare and difficult to diagnose, and to perform literature review, describing the most relevant aspects and the main controversies. Method. Report of a case and search in PubMed on June 1, 2015, using the terms "Appendix" [MeSH term] AND "hernia, inguinal" [MeSH term]. Results. The search resulted in 38 articles in total, and after deleting the articles that were not part of the inclusion criteria, there were 26 case reports remaining. Discussion. The search resulted in a total of 38 articles and after deleting the articles that were not part of the inclusion criteria, there were 26 case reports remaining. Conclusion. Amyand's hernia is a rare and difficult to diagnose condition, being commonly found occasionally in surgical procedures. It should be remembered in the presence of cases of incarcerated hernia, due to its possible complications if not diagnosed.